Peran Metakognisi dalam Pendidikan Karakter: Studi Kasus tentang Strategi Pembentukan Moral dan Etika Siswa - Endang Purwaningsih (Society, 2024)
Character education is essential in shaping students’ morals and ethics. This study aims to examine the role of metacognition in character education through a comprehensive literature review. Metacognition, encompassing metacognitive knowledge and skills, enhances the effectiveness of character education by providing strategies such as self-reflection, goal setting, self-monitoring, and self-assessment. The research employs a literature review approach, selecting articles and studies from credible and relevant sources. Data analysis addresses the main question of how metacognitive strategies can be applied to shape students’ morals and ethics. Key findings indicate that metacognition significantly contributes to character education, although challenges such as limited teacher understanding and resource constraints persist. Identified opportunities include developing teacher training programs focused on metacognition and character education and the potential for improved student learning outcomes. This study concludes that integrating metacognition into character education not only enhances the formation of students’ morals and ethics but also offers practical strategies for implementation in schools. Practical recommendations and areas for further research are presented for ongoing development in this field.